Elevated temperatures and longer durations improve the efficacy of oxaliplatin- and mitomycin C-based hyperthermic intraperitoneal chemotherapy in a confirmed rat model for peritoneal metastasis of colorectal cancer origin - Helderman, Roxan F. C. P. A.; Bokan, Bella; van Bochove, Gregor G. W.; Rodermond, Hans M.; Thijssen, Elsy; Marchal, Wouter; Torang, Arezo; Löke, Daan R.; Franken, Nicolaas A. P.; Kok, H. Petra; Tanis, Pieter J.; Crezee, Johannes; et al. (Frontiers in Oncology, 2023)
In patients with limited peritoneal metastasis (PM) originating from colorectal cancer, cytoreductive surgery (CRS) followed by hyperthermic intraperitoneal chemotherapy (HIPEC) is a potentially curative treatment option. This combined treatment modality using HIPEC with mitomycin C (MMC) for 90 minutes proved to be superior to systemic chemotherapy alone, but no benefit of adding HIPEC to CRS alone was shown using oxaliplatin-based HIPEC during 30 minutes. We investigated the impact of treatment temperature and duration as relevant HIPEC parameters for these two chemotherapeutic agents in representative preclinical models. The temperature- and duration- dependent efficacy for both oxaliplatin and MMC was evaluated in an in vitro setting and in a representative animal model. In 130 WAG/Rij rats, PM were established through i.p. injections of rat CC-531 colon carcinoma cells with a signature similar to the dominant treatment-resistant CMS4 type human colorectal PM. Tumor growth was monitored twice per week using ultrasound, and HIPEC was applied when most tumors were 4-6 mm. A semi-open four-inflow HIPEC setup was used to circulate oxaliplatin or MMC through the peritoneum for 30, 60 or 90 minutes with inflow temperatures of 38°C or 42°C to achieve temperatures in the peritoneum of 37°C or 41°C. Tumors, healthy tissue and blood were collected directly or 48 hours after treatment to assess the platinum uptake, level of apoptosis and proliferation and to determine the healthy tissue toxicity. In vitro results show a temperature- and duration- dependent efficacy for both oxaliplatin and MMC in both CC-531 cells and organoids. Temperature distribution throughout the peritoneum of the rats was stable with normothermic and hyperthermic average temperatures in the peritoneum ranging from 36.95-37.63°C and 40.51-41.37°C, respectively. Treatments resulted in minimal body weight decrease (<10%) and only 7/130 rats did not reach the endpoint of 48 hours after treatment. Both elevated temperatures and longer treatment duration resulted in a higher platinum uptake, significantly increased apoptosis and lower proliferation in PM tumor lesions, without enhanced normal tissue toxicity. Our results demonstrated that oxaliplatin- and MMC-based HIPEC procedures are both temperature- and duration-dependent in an in vivo tumor model.